A Book of Waves - Helmreich, Stefan, 1966- (Book collections on Project MUSE., 2023)
"In A Book of Waves Stefan Helmreich examines ocean waves as forms of media that carry ecological, geopolitical, and climatological news about our planet. Drawing on ethnographic work with oceanographers and coastal engineers in the Netherlands, the United States, Australia, Japan, and Bangladesh, Helmreich details how scientists at sea and in the lab apprehend waves' materiality through abstractions, seeking to capture in technical language these avatars of nature at once periodic and irreversible, wild and pacific, ephemeral and eternal. For researchers and their publics, the meanings of waves also reflect visions of the ocean as an environmental infrastructure fundamental to trade, travel, warfare, humanitarian rescue, recreation, and managing sea level rise. Interleaving ethnographic chapters with reflections on waves in mythology, surf culture, feminist theory, film, Indigenous Pacific activisms, Black Atlantic history, cosmology, and more, Helmreich demonstrates how waves mark out the wakes and breaks of social histories and futures"--